VARIOUS TYPES OF DEBT: MAWARIS FIQH REVIEW - Badrah Uyuni; Mohammad Adnan (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2020)
Debt is muamalah which is allowed in Islam. Debt can bring someone to heaven because of their intention to help fellow humans (hablun minannaas) but debt can also bring someone into hellfire when it is not managed properly. Problems due to accounts payable often arise because debtors and borrowers do not pay attention to the manners in debt. Therefore, debt needs to be managed by paying attention to Islamic instructions both as contained in the Koran and in the alhadits so that the activities of accounts payable can bring blessings and become a solution for the ummah. This article is an introduction to the various types of debt in the Fiqh mawaris review. Various arguments and logics of fiqh are placed to understand that debt is an important study. As for the obligations towards Allah that have not been fulfilled such as zakat, going on hajj, paying for kafarah, it is also called debt, by jazy, not haqiqy, because the obligation to fulfill these things is not as a reward for an achievement that has been received by someone, but as fulfillment of obligations that are required when someone is still alive.